Enlivening a place brand inclusively: evidence from ten European cities - Lemmetyinen, Arja; Nieminen, Lenita; Aalto, Johanna; Pohjola, Tuomas (Palgrave Macmillan, 2025)
This study contributes to the stream of research investigating the influence of the creative sector on the development of cities and the importance of place branding to local development. Place branding increasingly influences the competitiveness and attractiveness of cities. We examined ten European cities as creative places and how integrating creative economy strategies, social inclusion, and sustainable practices into city branding contributes to differentiation and competitiveness. The current research contributes to the research area by examining certain cities in the context of the creative economy and investigating how, as creative brands, they can be differentiated from their competitors by utilizing inclusive planning of the image of the place.